Pembaharuan Pemikiran Islam: Sebuah Konstruksi Intelektualisme Kesarjanaan Qur’an-Hadis - Kusmana Kusmana (Institut Agama Islam Negeri (IAIN) Curup, 2022)
Renewal of Islamic Thought: A Construction of Qur'an-Hadith scholarly intellectualismThis research is a construction of Islamic thought reform in the case of the Qur’anic and Hadith studies. It aims at mapping the construction of intellectualism in the Qur’an and Hadith scholarship. Descriptive-analytic method is used in this study, tracing the renewal of Islamic thought in history. This study finds that rhetorical Islamic scholarship dominated the discourse and practice of Islamic teachings and scholarship. In other words, with the addition of Salafi Islamic langue structure, the task of renewing Islamic thought confronts the hermeneutics of Islamic orthodoxy along with the institutions and agencies that support it. This results in the task of renewing Islamic thought not easily. Various attempts have been made and are being pursued by Islamic renewal thinkers with three variations of expressions and proposals for renewal. First, thinkers who approach the study of Islamic thought from a perspective outside of religious sources (the Qur'an and Hadith), the second group of Muslim thinkers who approach the study of Islamic thought from the perspective of internal sources of religion, and the third group of them who study it by combining various thought traditions